Comparison of the Effectiveness of Compassion-Focused Therapy and Mindfulness-Based Cognitive Therapy on Sexual Function and Quality of Life in Women with Hypothyroidism - Parsapour , Sepideh; Raeisi, Zohreh; Rajnbar Kohan, Zohreh; Rezaei‑Jamalouei, Hasan (Psychology of Woman Journal, 2025)
Objective: The present study aimed to compare the effectiveness of compassion-focused therapy and mindfulness-based cognitive therapy on sexual function and quality of life in women with hypothyroidism. Materials and Methods: The study was a semi-experimental research with a pre-test-post-test design and a control group. The statistical population consisted of women with hypothyroidism who visited the Endocrinology Clinic of the Isfahan University of Medical Sciences in the second half of 2023. From this population, 45 participants were selected through accessible sampling and randomly assigned to the experimental group of compassion-focused therapy (15 participants), the experimental group of mindfulness-based cognitive therapy (15 participants), and the control group (15 participants). Data collection tools included the Rosen and colleagues (2000) Female Sexual Function Questionnaire and the World Health Organization (1996) Quality of Life Questionnaire. The compassion-focused therapy group received Gilbert’s (2009) intervention package, while the mindfulness-based cognitive therapy group received Crane’s (2009) intervention package for eight 90-minute sessions. The data were analyzed using multivariate analysis of variance (MANOVA) and the LSD post-hoc test. Findings: The results indicated a significant difference in the effectiveness of the two therapeutic approaches on sexual function in women with hypothyroidism. According to the post-hoc test, mindfulness-based cognitive therapy had a significantly greater effect on improving sexual function than compassion-focused therapy. However, no significant difference was found between the two therapies in terms of their impact on quality of life. Conclusion: Mindfulness-based cognitive therapy can be considered a useful therapeutic strategy for improving the psychological condition of women with hypothyroidism.